2012
DOI: 10.1007/s11665-012-0127-1
|View full text |Cite
|
Sign up to set email alerts
|

Control of Interfacial Reactivity Between ZrB2 and Ni-Based Brazing Alloys

Abstract: Transition metals diborides (Ti,Zr,Hf)B 2 play a key role in applications where stability at extremely high temperatures and damage tolerance are required; however, much research has still to be done to optimize the joining of these materials to themselves or to other high-temperature materials. In this study, the reactivity at the solid-liquid interface between ZrB 2 ceramics and Ni-based brazing alloys has been addressed; it is shown how the reactivity and the dissolution of the solid phase can be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…For example, Ni with SiC forms Ni 2 Si, and although the reaction of ZrB 2 with Ni to form nickel borides, Ni 2 B and Ni 3 B, has a positive ΔG, Ni 2 B formation has been identified by electron probe microanalysis in the Au‐Ni/ZrB 2 system . Recent studies by Passerone and coworkers have shed much light on the interfacial reactions and contact angles of UHTCs and molten pure metals. The major constituents, Ti, Zr, Cu, and Ni, of the Ti‐375 and Ti‐120 brazes used in the present study, all wet ZrB 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ni with SiC forms Ni 2 Si, and although the reaction of ZrB 2 with Ni to form nickel borides, Ni 2 B and Ni 3 B, has a positive ΔG, Ni 2 B formation has been identified by electron probe microanalysis in the Au‐Ni/ZrB 2 system . Recent studies by Passerone and coworkers have shed much light on the interfacial reactions and contact angles of UHTCs and molten pure metals. The major constituents, Ti, Zr, Cu, and Ni, of the Ti‐375 and Ti‐120 brazes used in the present study, all wet ZrB 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, ductile metallic brazes may be used to join the UHTC to metal alloys. Currently, there is considerable interest in joining of UHTCs as evidenced by a number of scientific studies focusing on wetting, interfacial phenomena, and brazing of UHTCs, including contact angle measurements for diboride ceramics in contact with Ag, Cu, Au, Co, and Ni . Nickel‐based brazes, Ag–Cu–Ti brazes, Pd‐based brazes, and other brazes have been used to join the UHTCs …”
Section: Introductionmentioning
confidence: 99%
“…Also, Ni-B alloys are effective in reducing ceramic dissolution, compared to pure Ni ( Ref 24,25). Wettability and interfacial interactions have been extensively studied for Ni-B alloys and ZrB 2 and HfB 2 ceramics (Ref [24][25][26][27]. Those results showed that dissolution of these ceramics can be controlled by adjusting Ni-B composition.…”
Section: Introductionmentioning
confidence: 99%
“…The common methods employed to improve the wettability and adhesion at the heterogeneous ceramic-ceramic and metal-ceramic interfaces involve physical and chemical modification of the interfaces via deposition of a low-melting and/or a reactive metal. 10,11 Given that the operation life-time and performance of any of these structural materials systems depend on the thermo-mechanical and chemical stabilities of the interfaces, a fundamental knowledge of the interfacial thermodynamics and reaction-diffusion kinetics is valuable. Here, we focus on the thermal stability of ZrB 2 in contact with metals such as Pt and Mo.…”
mentioning
confidence: 99%
“…6,12 Typically, these structural components are prepared out of ceramic powders, which are mixed with metals or metal silicides to promote sintering and to enhance their functionality. 8,11,[13][14][15][16][17][18][19] Growth and characterization of ZrB 2 thin films are also of interest for potential applications as decorative coatings and diffusion barriers in microelectronics. 20,21 In this letter, we report results from in situ transmission electron microscopy (TEM) studies of thermal stability of ZrB 2 thin films in contact with Pt and Mo.…”
mentioning
confidence: 99%